Serum metabolites and risk of sudden sensorineural hearing loss: A Mendelian randomization study - Wenhui Yuan; Yong Liu; Chao Liu; Yuanzheng Qiu (Brazilian Journal of Otorhinolaryngology)
Objective: Observational studies found that Sudden Sensorineural Hearing Loss (SSNHL) is associated with metabolic disorders, but the causal relationship remains unclear. Here we performed a two-sample Mendelian Randomization (MR) analysis to systematically assess the causation between blood metabolites and SSNHL. Methods: Summary statistics for blood metabolites were extracted from GWAS data of 7824 European participants on metabolite levels. GWAS data for SSNHL were collected from the FinnGen Consortium R10 release data, which consisted of 3128 cases and 362,353 controls in European populations. The inverse variance weighted method was the primary method for causality analysis while MR-Egger, weighted median and MR-RAPS served as complementary approaches. Cochran’sQ test, MR-Egger intercept test, MR-PRESSO, Radial MR, leave-one-out and Steiger test were used for sensitivity analyses. Additionally, we performed metabolic pathway analysis to further explore the potential pathogenesis of SSNHL. Results: We found that genetically predicted cholesterol, citrate, myristoleate (14:1n5) and tryptophan betaine may increase the risk of SSNHL, while stearate (18:0), pantothenate and glycerol 2-phosphate may act as protective factors for SSNHL. Nevertheless, these metabolites did not reach statistical significance after Bonferroni correction. Sensitivity analyses revealed no evidence of heterogeneity or horizontal pleiotropy. Metabolic pathway analysis revealed the pantothenate and CoA biosynthesis pathway and the citrate cycle pathway potentially related to the pathogenesis of SSNHL. Conclusion: The findings of our study offer new insights into the role of blood metabolites in the development and pathogenesis of SSNHL and provide potential inspiration for further advancements in clinical settings. Level of evidence: Level 3.